Do social and economic reforms change socioeconomic inequalities in child mortality? A case study: New Zealand 1981–1999. Issue 8 (14th July 2005) - Shaw, Caroline; Blakely, Tony; Atkinson, June; Crampton, Peter
Abstract : Background: Socioeconomic inequalities in child mortality are known to exist; however the trends in these inequalities have not been well examined. This study examines the trends in child mortality inequality between 1981 and 1999 against the background of the rapid and dramatic social and economic restructuring in New Zealand during this time period. Methods: Record linkage studies of census and mortality records of all New Zealand children aged 0–14 years on census night 1981, 1986, 1991, 1996, each followed up for three years for mortality between ages 1–14 years. Socioeconomic position was measured using maternal education, household income, and highest occupational class in the household. Standardised mortality rates, rate ratios, and rates differences as well as regression based measures of inequality were calculated. Results: Mortality in all socioeconomic groups fell between 1981 and 1999. Socioeconomic inequality in child mortality existed by all measures of socioeconomic position, however only trends by income suggested a change over time: the relative index of inequality increased from 1.5 in 1981–84 to 1.8 in 1996–99 (p trend 0.06), but absolute inequality remained stable (slope index of inequality 15/100 000 in 1981–84 and 14/100 000 in 1996–99. Conclusions: Dramatic changes in income in New Zealand possibly translated into increasing relative inequality in child mortality by income, but not by education or occupational class. The a priori hypothesis that socioeconomic inequalities in child mortality would have increased in New Zealand during a period of rapid structural reform and widening income inequalities was only partly supported.